Analisis Dukungan Keluarga, Tingkat Pengetahuan, dan Keterjangkauan Akses ke Pelayanan Kesehatan terhadap Penerapan Program Patuh Lansia Hipertensi - Katrina Feby Lestari; Sri Yulianti; Juwita Meldasari Tebisi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to analyze the relationship between family support, level of knowledge, and affordability of access to health services with the implementation of the hypertensive elderly PATUH program in the Anuntodea Tipo Health Center working area. This study uses a quantitative method with an analytic design and a cross-sectional approach. The results showed family support (p-value = 0.007), level of knowledge (p-value = 0.051), and affordability of access to health services (p-value = 0.730). In conclusion, there is a significant relationship between family support and the implementation of the hypertensive elderly PATUH program in the Work Area of the Anuntodea Tipo Health Center. There is no relationship between the level of knowledge and affordability of access to health services with the implementation of the hypertensive elderly PATUH program in the Work Area of the Anuntodea Tipo Health Center. Keywords: Support, Knowledge, Access, PATUH Program